Macro-Modelling for the Eleventh Five Year Plan of India - Planning Commission (Planning Commission)
Planning was introduced in the country because of a number of reasons: In a country with large disparity of incomes and wealth, a competitive market would not lead to a socially desirable outcome. Scarce investible resource and foreign exchange should be directed in socially desirable activities, which required government activism. Development of infrastructure involved long gestation and required technology and large investments which the private sector was not capable of undertaking. The diversity of the country required a regionally balanced development.
Perspective Planning Division, Planning Commission, Government of India